2023
DOI: 10.1103/physrevlett.130.216802
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Nematic-Isotropic Liquid Critical End Point

Abstract: A critical end point above which an isotropic phase continuously evolves into a polar (ferroelectric) nematic phase with an increasing electric field is found in a ferroelectric nematic liquid crystalline material. The critical end point is approximately 30 K above the zero-field transition temperature from the isotropic to nematic phase and at an electric field of the order of 10 V=μm. Such systems are interesting from the application point of view because a strong birefringence can be induced in a broad temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The high fluidity of the N F phase combined with its polar properties immediately caught the attention of scientists around the world due to not only its huge application potential but also its fundamental significance as a spontaneously ferroelectric fluid. The N F phase became one of the hottest topics in liquid crystal research. Owing to the fluid nature of the N F phase, a uniform polarization direction can be obtained in large areasa key to realizing its application potential . However, the question arises whether the competitive interactions that drive the formation of the N F phase can also lead to other complex structures as is the case with the improper ferroelectric liquid crystal phases.…”
Section: Introductionmentioning
confidence: 99%
“…The high fluidity of the N F phase combined with its polar properties immediately caught the attention of scientists around the world due to not only its huge application potential but also its fundamental significance as a spontaneously ferroelectric fluid. The N F phase became one of the hottest topics in liquid crystal research. Owing to the fluid nature of the N F phase, a uniform polarization direction can be obtained in large areasa key to realizing its application potential . However, the question arises whether the competitive interactions that drive the formation of the N F phase can also lead to other complex structures as is the case with the improper ferroelectric liquid crystal phases.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown potential microscopic origins of spontaneous polarity and revealed the roles of steric and electric-field effects on the stability of polar states. 18–23 In terms of symmetry, the N state and the polar counterpart, the N F state, belong to the D ∞h and C ∞v point groups, respectively. 7 Practically, the realization of the polar states is made by introducing strong dipole moments to rod-shaped molecules.…”
Section: Introductionmentioning
confidence: 99%